The Application of Restorative Justice in Domestic and Child Violence Cases in Indonesia and Finland - Hamamah, Fatin; Sukardi, Didi; Kulkarni, Shirin (SASI, 2025)
Introduction: Restorative justice (RJ) is an alternative approach to criminal justice that focuses on victim recovery, offender rehabilitation and community reintegration. In the context of domestic and child violence, this approach offers the potential for more inclusive and sustainable solutions than traditional retributive approaches. However, there is debate about the effectiveness of RJ in cases of violence that have profound psychological and physical impacts on victims. The issue is whether RJ can provide adequate justice without compromising legal protections for victims. This research offers novelty by examining the application of RJ in cases of domestic and child violence in Indonesia and Fnland, where RJ laws and policies are still developing.Purposes of the Research:  The purpose of the study was to identify the challenges and opportunities for the application of RJ in such cases and evaluate the extent to which this approach is able to create restorative justice for victims and perpetrators in Indonesia and Finland.Methods of the Research: The research used qualitative methods with case studies of several domestic and child violence cases resolved through RJ in different regions.Results / Main Findings / Novelty/Originality of the Research: Findings suggest that RJ can be effective in facilitating victim recovery, but its implementation requires strong support structures, including professional counsellors and clear legal protections in Indonesia and Finland. The conclusions of this study confirm that RJ has great potential in resolving domestic violence cases, but its implementation must be done carefully to ensure justice and protection for victims. Consequently, this research encourages policymakers to design a more comprehensive and inclusive RJ framework for domestic violence.